A new second-generation supraglottic airway device (Ambu® AuraGain•) versus intubating laryngeal mask airway as conduits for blind intubation – A prospective, randomised trial - K Sudheesh; G M Chethana; H Chaithali; S S Nethra; D Devikarani; G Shwetha (Indian Journal of Anaesthesia, 2019)
Background and Aims: The Ambu® AuraGain• is a new single-use supraglottic airway device with gastric channel, designed to facilitate intubation. The study aimed to assess the success rates of proper placement and intubation using Ambu® AuraGain• compared with intubating laryngeal mask airway (ILMA). Methods: One hundred and twenty patients (18–60 years) were enrolled into this prospective, randomised, comparative study. After inducing general anaesthesia, appropriate size ILMA (group I)/Ambu® AuraGain• (group A) was placed as per the manufacturer's recommendations and correct placement was confirmed. Appropriate size endotracheal tube was passed through the device. The success rate of insertion and intubation, number of attempts, Cormack–Lehane grading before insertion and haemodynamics were recorded. Data were analysed using Mantel–Haenszel Chi-square test, Student's t-test and Fisher's exact test. Results: Demographic and airway parameters were uniformly distributed in both the groups. The success rate for insertion was 100% in both devices. The success rate for intubation was 96.6% (58/60) in group I and 36.6% in group A (P < 0.001). In group I, patients with mean thyromental distance >7.62 ± 0.75 cm had higher successful intubation compared with patients with mean thyromental distance <5.25 ± 0.35 cm (P = 0.014). Cormack–Lehane grading did not correlate with intubation attempts or success rate in group I (P = 0.45), whereas in group A the rate of successful blind intubation with Cormack–Lehane grade 1 was 50% (19/38). Conclusion: Both devices have 100% insertion success, though Ambu® AuraGain• has lower success rate for facilitating intubation compared with ILMA.